Optical spectroscopy and local structure of the Nd3+ luminescence centres in glasses of the CaO–Ga2O3–GeO2 system - Padlyak, Bohdan; Ryba-Romanowski, Witold; Lisiecki, Radosław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Optical absorption and luminescence spectra as well as luminescence kinetics of the Nd3+ centres in glasses with Ca3Ga2Ge3O12:Nd composition, containing 0.2 and 1.0 wt% of the Nd2O3 were presented and analysed. The oscillator strengths and phenomenological intensity parameters Ωt (Ω2, Ω4, and Ω6) were obtained using standard Judd–Ofelt theory. Calculated Ωt parameters, radiative transitions rates, branching ratios and radiative lifetime for Nd3+ centres in the glass with Ca3Ga2Ge3O12 composition were analysed and compared with corresponding Nd3+ parameters in their crystalline analogue with garnet structure. Experimental lifetimes are compared with those calculated, and quantum efficiency of Nd3+ centres from 4F3/2 emitting level in the glass with Ca3Ga2Ge3O12 composition is estimated. Incorporation peculiarities and local structure of Nd3+ luminescence centres in the glass with Ca3Ga2Ge3O12 composition and corresponding Ca3Ga2Ge3O12:Nd3+ garnet laser crystals are considered. On the basis of extended X-ray absorption fine structure (EXAFS) spectra (L3-edge) of rare-earth elements analysis it has been shown that Nd3+ luminescence centres in the CaO–Ga2O3–GeO2 glass network occupy structural sites with the coordination number to oxygen N = 6.
Optica Applicata, Vol. 38, 2008, nr 1, s. 189-202
Keywords: optyka; germanate glasses; Nd3+ centre; optical absorption; luminescence; decay kinetics; extended X-ray absorption fine structure (EXAFS); local structure